2014
DOI: 10.1093/jnci/dju286
|View full text |Cite
|
Sign up to set email alerts
|

Terminal Duct Lobular Unit Involution of the Normal Breast: Implications for Breast Cancer Etiology

Abstract: Morphometric analysis of TDLU involution warrants further evaluation to understand the pathogenesis of breast cancer and assessing its role as a progression marker for women with benign biopsies or as an intermediate endpoint in prevention studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
99
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 73 publications
(121 citation statements)
references
References 48 publications
21
99
1
Order By: Relevance
“…H&E stained tissue sections were digitized at 20× magnification (Aperio ScanScope CS, Vista, CA), and prepared for web-based viewing and annotation with Digital Image Hub software (SlidePath/Leica, Dublin, Ireland) (12). The lasso tool in Digital Image Hub was used to manually outline and measure total tissue area (mm 2 ) per section.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…H&E stained tissue sections were digitized at 20× magnification (Aperio ScanScope CS, Vista, CA), and prepared for web-based viewing and annotation with Digital Image Hub software (SlidePath/Leica, Dublin, Ireland) (12). The lasso tool in Digital Image Hub was used to manually outline and measure total tissue area (mm 2 ) per section.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously found quantitative measures that are inversely associated with TDLU involution (i.e., TDLU count, median TDLU span, and median acini count/TDLU) to be significantly related to breast cancer risk factors among women who donated normal breast tissues (12). In a separate study of women undergoing diagnostic breast biopsy, we determined that risk factor associations with quantitative area and volumetric MD measures exhibited some overlap but divergence as well, particularly for BMI (13).…”
Section: Introductionmentioning
confidence: 99%
“…One sample was fixed in 10% buffered formalin, routinely processed to prepare paraffin embedded blocks, sectioned at 5 μm, and stained with hematoxylin and eosin. Digitized images of these sections were used for analysis of percent fat on tissue slide (≤50%, 51-75%, and >75%) and measurements of TDLU involution are described in detail elsewhere (15). …”
Section: Methodsmentioning
confidence: 99%
“…We developed three reproducible TDLU involution measures, based on morphometric TDLU assessment (i.e., TDLU counts, span, and acini counts per TDLU), which are inversely associated with TDLU involution (15). Assessment of these measures among women in the Susan G. Komen Tissue Bank at the Indiana University Simon Cancer center (KTB), a unique resource of normal breast tissue samples, blood samples, and clinical data, found older age, parity, and menopausal status amongst the predominant characteristics associated with TDLU involution.…”
Section: Introductionmentioning
confidence: 99%
“…TDLUs are the structures of the breast that produce milk and also give rise to breast cancer precursors. TDLUs undergo a range of morphological changes related to puberty, pregnancy, lactation, aging, and menopause,[133, 134] and can also accompany altered molecular histology and a change in mammographic density. Studies have found that, among women with benign breast biopsy, reduced levels of TDLU involution in the surrounding normal breast are associated with breast cancer risk.…”
Section: Pathology and Pathogenesismentioning
confidence: 99%